The relative importance of trust and usable website design in building e-loyalty intention on internet banking : a case of Maybank2U.com - Abdul Hamid, Nor Aziati (2005)
In e-commerce, loyal customers are considered extremely valuable. The high cost of attracting new customers on the Internet and the relative difficulty in retaining them make customer loyalty an essential asset for many banks. Since online transactions involve many uncertainties for the customer and most of the Internet banking offers the same product as the other competitor, it is crucial for banks to recognize the key factor that can tie their existing customer become a loyal customer an change the web surfers into purchaser. Despite of increasing usage of Internet Shopping and banking, the literature only portray little effort of empirical research has addressed the role of quality Internet websites design and customer online trust in forming consumers' intentions to revisits or repurchase particular products or at particular banks within the context of customer relationship management. This empirical study was performed to measure relative importance of two different factor that is most cited as a critical success factor for ecommerce environment; usable website design and trust elements on the website. The study specifically focuses on Maybank2u.com users and sample for the study was drawn among academician and students of three different faculties in UiTM Shah Alam. The results of the empirical analysis confirmed that the trust of the user increases when the user perceived that the website was usable and that there was a consequent increase in the degree of website loyalty